Mapping musical dynamics in space. A qualitative analysis of conductors' movements in orchestra rehearsals - Meissl, Katharina; Sambre, Paul; Feyaerts, Kurt (Frontiers in Communication, 2022)
In this contribution, we examine the way in which orchestra conductors use the space around them to convey aspects of musical dynamics. In music, dynamics refers to “the intensity of volume with which notes and sounds are expressed” (Thiemel, 2001) and its interpretation is highly context-bound (Weeks, 1996, 248). We approach dynamics as a phenomenon of emergent and construed meaning in interaction, induced by the music score and the interpretation in situ by musicians and the conductor. Conductors’ movement-based instructions on dynamics result in highly complex usage events. This study aims at disentangling these instances by asking how conductors move and use the space around them to instruct on (un)desired aspects of musical dynamics, zooming in on movement direction as a central formal feature. We find ourselves at the crossroads of cognitive and interactional linguistics, aligning with existing studies on the interactional and contextually embedded nature of music interaction (cf. Parton, 2014). From a cognitive linguistic perspective, this endeavour translates as the identification of the construal mechanisms (metaphor, specificity and viewpoint) that underlie and therefore motivate movement directions in the specific instances under examination. The analysis is based on ten hours of video data from a corpus recorded during rehearsals of five conductors instructing their respective orchestras in Dutch ([author], 2020). Our data reveal that conductors use different movement patterns, some of which appear to involve opposite movement directions for expressing a similar music dynamical aspect, e.g. depending on the usage event, a vertical upward movement can mean both a request for playing louder and softer. By taking into account different construal mechanisms, we are able to provide an encompassing multimodal analysis, in which these allegedly deviating oppositional movements appear as consistently motivated (metaphorical) expressions, which profile a similar target concept involving different viewpoints.